Depolarizing GABA Transmission Restrains Activity-Dependent Glutamatergic Synapse Formation in the Developing Hippocampal Circuit - Salmon, Christopher K.; Pribiag, Horia; Gizowski, Claire; Farmer, W. Todd; Cameron, Scott; Jones, Emma V.; Mahadevan, Vivek; Bourque, Charles W.; Stellwagen, David; Woodin, Melanie A.; Murai, Keith K. (Frontiers in Cellular Neuroscience, 2020)
GABA is the main inhibitory neurotransmitter in the mature brain but has the paradoxical property of depolarizing neurons during early development. Depolarization provided by GABA¬A transmission during this early phase regulates neural stem cell proliferation, neural migration, neurite outgrowth, synapse formation, and circuit refinement, making GABA a key factor in neural circuit development. Importantly, depending on the context, depolarizing GABAA transmission can either drive neural activity, or inhibit it through shunting inhibition. The varying roles of depolarizing GABAA transmission during development, and its ability to both drive and inhibit neural activity, makes it a difficult developmental cue to study. This is particularly true in the later stages of development, when the majority of synapses form and GABAA transmission switches from depolarizing to hyperpolarizing. Here we addressed the importance of depolarizing but inhibitory (or shunting) GABAA transmission in glutamatergic synapse formation in hippocampal CA1 pyramidal neurons. We first showed that the developmental depolarizing-to-hyperpolarizing switch in GABAA transmission is recapitulated in organotypic hippocampal slice cultures. Based on the expression profile of K+-Cl- co-transporter 2 (KCC2) and changes in the GABA reversal potential, we pinpointed the timing of the switch from depolarizing to hyperpolarizing GABAA transmission in CA1 neurons. We found that blocking depolarizing but shunting GABAA transmission increased excitatory synapse number and strength, indicating that depolarizing GABAA transmission can restrain glutamatergic synapse formation. The increase in glutamatergic synapses was activity-dependent, but independent of BDNF signalling. Importantly, the elevated number of synapses was stable for more than a week after GABAA inhibitors were washed out. Together these findings point to the ability of immature GABAergic transmission to restrain glutamatergic synapse formation and suggest an unexpected role for depolarizing GABAA transmission in shaping excitatory connectivity during neural circuit development.